-Tyrosine Confers Residualizing Properties to a -Amino Acid-Rich Residualizing Peptide for Radioiodination of Internalizing Antibodies - Fook T. Lee PhD; Ingrid J. G. Burvenich PhD; Nancy Guo MBBS, MSc; Pece Kocovski BSc (Honors); Henri Tochon-Danguy PhD; Uwe Ackermann PhD; Graeme J. O’Keefe PhD; Sylvia Gong PhD; Angela Rigopoulos BSc, MSc; Zhanqi Liu MBBS, PhD; Hui K. Gan MBBS, FRACP, PhD; Andrew M. Scott MBBS, FRACP, MD (Molecular Imaging)
Purpose: The aims of the study were to develop and evaluate a novel residualizing peptide for labeling internalizing antibodies with 124 I to support clinical development using immuno-positron emission tomography (PET). Methods: The anti-epidermal growth factor receptor antibody ch806 was radiolabeled directly or indirectly with isotopes and various residualizing peptides. Azido-derivatized radiolabeled peptides were conjugated to dibenzylcyclooctyne-derivatized ch806 antibody via click chemistry. The radiochemical purities, antigen-expressing U87MG.de2-7 human glioblastoma cell-binding properties, and targeting of xenografts at 72 hours post injection of all radioconjugates were compared. Biodistribution of 124 I-PEG 4 -tptddYddtpt-ch806 and immuno-PET imaging were evaluated in tumor-bearing mice. Results: Biodistribution studies using xenografts at 72 hours post injection showed that 131 I-PEG 4 -tptddYddtpt-ch806 tumor uptake was similar to 111 In-CHX-A″-DTPA-ch806. 125 I-PEG 4 -tptddyddtpt-ch806 showed a lower tumor uptake value but higher than directly labeled 125 I-ch806. 124 I-PEG 4 -tptddYddtpt-ch806 was produced at 23% labeling efficiency, 98% radiochemical purity, 25.9 MBq/mg specific activity, and 64% cell binding in the presence of antigen excess. Tumor uptake for 124 I-PEG 4 -tptddYddtpt-ch806 was similar to 111 In-CHX-A″-DTPA-ch806. High-resolution immuno-PET/magnetic resonance imaging of tumors showed good correlation with biodistribution data. Conclusions: The mixed d / l -enantiomeric peptide, d Thr- d Pro- d Thr- dA sp -dA sp-Tyr -dA sp -dA sp- d Thr- d Pro- d Thr, is suitable for radiolabeling antibodies with radiohalogens such as 124 I for high-resolution immuno-PET imaging of tumors and for evaluation in early-phase clinical trials.